2008
DOI: 10.1039/b719927a
|View full text |Cite
|
Sign up to set email alerts
|

A general and efficient method to form self-assembled cucurbit[n]uril monolayers on gold surfaces

Abstract: A general protocol based on spontaneous adsorption of cucurbit[n]uril (CB[n]) molecules through a strong multivalence interaction between CB[n] and gold is described, by which the formation of self-assembled CB[n] monolayers on gold surfaces can be efficiently achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 27 publications
6
72
0
Order By: Relevance
“…Complete mixing is achieved during the first channel corner (Figure S1, Supporting Information). Once the CB[5] and the AuNPs are mixed, the CB[5] binds the AuNPs together through interactions between the Au surface and the carbonyl groups of the CB portals . The CB[5]:AuNP concentration ratio places the assembly in a diffusion‐limited assembly regime (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Complete mixing is achieved during the first channel corner (Figure S1, Supporting Information). Once the CB[5] and the AuNPs are mixed, the CB[5] binds the AuNPs together through interactions between the Au surface and the carbonyl groups of the CB portals . The CB[5]:AuNP concentration ratio places the assembly in a diffusion‐limited assembly regime (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[68] Li and coworkers made noncovalent CB[n] SAMs by spontaneously adsorbing of CB[n] cavities on gold surfaces utilizing the multivalent interactions between the lone-pairs of the carbonyls and the gold surface ( Figure 5b). [64] Surface-attached CB[n] molecules were found uniform in orientation and hold their carbonyls perpendicular with respect to the gold surface and their cavities open to the outer atmosphere or solution [64] This arrangement maintains the recognition properties of CB[n] and facilitates guest molecules to approach the cavities. However no binding affinities have been reported.…”
Section: Cb[n]-mediated Host-guest Chemistry On Surfacesmentioning
confidence: 99%
“…[58][59][60][61] In general, anchoring of CB[n] to surfaces has been achieved in different ways as depicted in Figure 5. [11,57,[62][63][64][65][66] When able to covalently functionalize the CB [7] macrocycle via covalent modification of CB[n] in a strongly oxidative environment to generate reactive perallyloxy sidegroups Kim and coworkers set out to employ these functional groups to covalently anchor CB [6] and CB [7] onto surfaces. Perallyloxy-CB [6] could be anchored via the thiol-ene reaction with thiol-functionalized glass slides to form a thioether bond between surface and macrocycle ( Figure 5a).…”
Section: Cb[n]-mediated Host-guest Chemistry On Surfacesmentioning
confidence: 99%
“…[21] To define the nature of the interactions responsible for the formation of the nanostructured Pd@CB-PN, we studied Pd@CB-PN by FTIR and XPS analysis. [17b] The XPS data showed a red shift of the oxygen (1s) peak at 531.5 eV and a new sulfur (2p) peak at 162.8 eV in Pd@CB-PN ( Figure S3), which can be assigned to the carbonyl oxygen interacting with Pd NPs [22] and sulfur in the Pd À S bond, [23] respectively. This, however, does not rule out the possible interaction between the carbonyl portal of the CB[6] units and the NPs since it has been reported that CB[6]-passivated Pd NPs also show no shifts in the C=O stretching vibration.…”
mentioning
confidence: 99%